STUDIES ON DIVERSITY AND ECOLOGY OF INVASIVE ALIEN FLORA IN MORADABAD DISTRICT - 1. Brajesh Kumar Singh, 2. Beena Kumari (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
A survey of invasive alien plant species in Moradabad was made and we found a total richness of 91 species belonging to 33 families. Dicots represented 81 species and monocots 10 species. About 46.15% of these alien species were introduced from tropical America followed Africa and South America. Maximum number of species (17) were from the family Asteraceae, followed by Amaranthaceae (9) and Euphorbiaceae (6) while grasses represented by 6 species. Herbs accounted for 58 species, undershrubs 5 species, shrubs 10 species, climbers 5 species, and Trees 5, whereas Grasses and Sedges represented 6 and 2 species respectively. The data revealed that both aquatic and terrestrial invasive plant species are becoming threat to the native flora as they reproduce rapidly and crowding out native species. Most of species are used for medicinal purpose in local area.